Carbon Ion Therapy Inhibits Esophageal Squamous Cell Carcinoma Metastasis by Upregulating STAT3 Through the JAK2/STAT3 Signaling Pathway - Luo, Hongtao; Yang, Zhen; Zhang, Qiuning; Shao, Lihua; Wei, Shihong; Liu, Ruifeng; Li, Zheng; Geng, Yichao; Li, Chengcheng; Wang, Xiaohu (Frontiers in Public Health, 2020)
Radiation therapy is an important component of the comprehensive treatment of esophageal cancer. However, conventional radiation resistance is one of the main reasons for treatment failure. The superiority of heavy ion radiation in physics and biology has been increasingly highlighted in radiation therapy research. Janus Kinase 2/Signal Transducer and Activator of Transcription 3 (JAK2/STAT3) pathway play an important role in the occurrence, development and metastasis of esophageal squamous cell carcinoma (ESCC) and are related to the development of ionizing radiation resistance in ESCC. Therefore, the aim of the present study was to investigate relationship between carbon ion inhibiting proliferation and metastasis of esophageal carcinoma cell and JAK2/STAT3 signal pathway.The result demonstrated that carbon ion beams can significantly reduce cell viability and stimulate apoptosis in human ESCC cells in a dose-dependent manner. In addition, carbon ion beams induced G2/M phase cell cycle arrest in ESCC cells and dose-dependently inhibited tumor metastasis. Additionally, poorly differentiated KYSE150 cells were more sensitive to the same carbon ion beam dose than moderately differentiated ECA109 cells. Carbon ion beam exposure regulated the relative expression of metastasis-related molecules at the transcriptional and translational levels in ESCC cells. Carbon ion beams also regulated E-cadherin and MMP2 in the downstream STAT3 pathway and inhibited ESCC cell metastasis, which activated the STAT3 signaling pathway. This study confirmed the inhibition of cell proliferation and the metastasis effect of carbon ion beam therapy in ESCC cells.